PEMBINAAN PEREMPUAN DI PEDESAAN DALAM BIDANG EKONOMI PRODUKTIF DI KABUPATEN LAMONGAN - yahya, yahya; Yulianto, Anton Eko (ABDIMAS NUSANTARA: Jurnal Pengabdian Kepada Masyarakat, 2022)
The purpose of fostering women in rural areas in the form of productive economic business training for women homeworkers carried out by the Lamongan Regency Women's Empowerment and Child Protection Service is to improve the economy and family welfare. This productive economic business training was attended by 75 participants consisting of: 1) Women homeworkers, and 2) Women cadres. The method of implementing the training was carried out by the lecture method, and question and answer. The results of the productive economic business training for women homeworkers: 1) The training participants have shown a desire to manage productive economic enterprises at the family and group level in their respective villages and or sub-districts, and 2) Participants are also enthusiastic about knowing and implementing strategies proper marketing for business continuity.